2015
DOI: 10.1016/j.ymgmr.2015.01.005
|View full text |Cite|
|
Sign up to set email alerts
|

First contiguous gene deletion causing biotinidase deficiency: The enzyme deficiency in three Sri Lankan children

Abstract: We report three symptomatic children with profound biotinidase deficiency from Sri Lanka. All three children presented with typical clinical features of the disorder. The first is homozygous for a missense mutation in the BTD gene (c.98_104 del7insTCC; p.Cys33PhefsX36) that is commonly seen in the western countries, the second is homozygous for a novel missense mutation (p.Ala439Asp), and the third is the first reported instance of a contiguous gene deletion causing the enzyme deficiency. In addition, this lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…If variant analysis fails to identify a variant(s) consistent with low enzymatic results, it is possible that the individual has a deletion of the BTD gene on one or both alleles. 92,93 Targeted variant testing is less commonly used given the ease of full-gene sequencing and may be most appropriate for family studies or prenatal diagnosis following sequencing of a proband. Optimal sample preparation, handling, and shipping with the inclusion of appropriate control samples can make molecular analysis unnecessary and eliminate the expense of repeated confirmatory testing.…”
Section: Test Interpretation and Reporting Interpretationmentioning
confidence: 99%
“…If variant analysis fails to identify a variant(s) consistent with low enzymatic results, it is possible that the individual has a deletion of the BTD gene on one or both alleles. 92,93 Targeted variant testing is less commonly used given the ease of full-gene sequencing and may be most appropriate for family studies or prenatal diagnosis following sequencing of a proband. Optimal sample preparation, handling, and shipping with the inclusion of appropriate control samples can make molecular analysis unnecessary and eliminate the expense of repeated confirmatory testing.…”
Section: Test Interpretation and Reporting Interpretationmentioning
confidence: 99%
“…Yet, besides the five most frequent variants reported, other variants affecting function or even variants of unknown significance can be found along the entire coding region of BTD, including exon 1 which was shown to be involved in a contiguous gene deletion reported recently. 6 It seems therefore more cost-effective to analyze the entire coding region at a time. A widely used method is the bi-directional gene sequencing of all four BTD exons and their flanking intronic sequences, which increases the detection rate to 99%; 4,10 this method is based either on Sanger sequencing of polymerase chain reaction products or high-throughput sequencing (HTS) targeting the regions of interest with a recommended minimal read depth of 30X and preferably of at least 100X.…”
Section: Methodsmentioning
confidence: 99%
“…Screening of large rearrangements is also relevant, as such an alteration was reported recently. 6 Recently, quantitative real-time reverse-transcription PCR was used to assess the role of an intronic variant altering BTD expression. 5 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). Furthermore, it has been reported that one child identified with a novel 107-kb contiguous deletion of three genes in homozygosity, including exon 1 of the BTD gene, the entire HACL1 gene, and the 5′ end of the adjacent COLQ gene exon 1, was profoundly affected for BTD (Senanayake et al 2015). These authors reported that at the time of evaluation, the child's symptoms were apparently solely attributable to the BTD and markedly improved with biotin supplementation (Senanayake et al 2015).…”
Section: Variant Interpretationmentioning
confidence: 99%